An Efficient Easy Computer Emergency Response Team Malware Reservoir System (eZCERT) - Madihah Mohd Saudi; Nurlida Basir; Farida Hazwani Mohd Ridzuan; Nabila, NF; Pitchay, SA (IEEE, 2024)
Prior conducting malware analysis, many researchers were facing difficulties to clean up the dataset and they took longer time to complete these processes due to lack of malware dataset that are free from any noise or any irrelevant data and lack of malware analysis skill. Therefore, an efficient Easy Computer Emergency Response Team Malware Reservoir System (eZCERT) has been developed to overcome such problems. It is a comprehensive and an efficient malwares incident handling system where it consists of standard operating procedures (SOP) for malware incident handling. It also has the capability to detect and respond to malware attacks. Furthermore, the novelty of this system is based on the integration of the incident response, apoptosis, case-based reasoning (CBR) and Knowledge Data Discovery (KDD). The evaluation testing result showed that the eZCERT managed to produce a better accuracy detection rate. Hence, this eZCERT can he used as the basis guideline for malware researchers in building malware dataset and doing malware analysis.